Representations in solving a word problem: The informal development of formal methods - Amado, Nélia (2011)
The aim of this paper is to analyse different types of representations used by grade 7 and 8 students in solving a word problem. The problem was offered to finalists of a mathematics contest held outside the classroom. The analysis of the products of different students show the key role of the representations used to solve the problem and how they are critical in the development of a sustainable process for informal learning of formal methods of solving systems of linear equations.